The Effect of Aswaja Values and Javanese Islam on Students' Moderate Islamic Thinking - Sunda, Yauma Trin; Fitri, Agus Zaenul (el Harakah: Jurnal Budaya Islam, 2022)
This article examines the issue of dialectical Islam with local culture in Indonesia, which eventually forms a distinctive and unique variant of Islam, as well as the acculturation of Aswaja values and Javanese Islam. Indonesian Islamic State Universities (UIN) are part of the component that forms a nationalist and religious generation. Undeniably, it is free from the Islamic variant of the times. The variant of Islam is not Islam which is separated from its purity, but Islam, which is acculturated with local culture. The study's mixed-method results showed that 72.4% of Aswaja's values influenced the formation of moderate thinking. Meanwhile, 42% of Javanese Islam also contributes to Moderate Islamic thought. As a variant of cultural Islam in Indonesia, Javanese Islam tends to be syncretic with its distinctive traditions. It can be seen in the dialectic of religion and culture, such as the “Grebek Pancasila”, the early Genduri of a sermon, and Wayang performances. Its substance is to transform the prophetic spirit of the teachings of monotheism while preserving local culture. Javanese Aswaja and Islamic values struggle with the realities of modernity and globalization. In this context, it can be seen how the response of groups of Islamic organizations, particularly the moderate Islam Rahmatan Lil Alamin. Artikel ini mengkaji persoalan dialektika Islam dengan budaya lokal di Indonesia yang pada akhirnya membentuk varian Islam yang khas dan unik, serta akulturasi nilai-nilai Aswaja dan Islam Jawa. Universitas Islam Negeri (UIN) di Indonesia merupakan bagian dari komponen yang membentuk generasi nasionalis dan agamis, yang tidak bisa dipungkiri terbebas dari varian Islam zaman. Varian Islam bukanlah Islam yang lepas dari kemurniannya, melainkan Islam yang berakulturasi dengan budaya lokal. Hasil penelitian dengan menggunakan metode campuran menunjukkan bahwa 72,4% nilai Aswaja mempengaruhi pembentukan berpikir moderat. Sementara itu, 42% Islam Jawa juga berkontribusi pada pemikiran Islam Moderat. Sebagai varian Islam budaya di Indonesia, Islam Jawa cenderung sinkretis dengan tradisi khasnya. Hal ini terlihat dalam dialektika agama dan budaya, seperti “Grebek Pancasila”, Genduri awal ceramah, dan pertunjukan wayang. Substansinya adalah mentransformasikan semangat profetik dari ajaran tauhid sekaligus melestarikan budaya lokal. Aswaja Jawa dan nilai-nilai Islam berjuang dengan realitas modernitas dan globalisasi. Dalam konteks ini, terlihat bagaimana respon kelompok ormas Islam, khususnya Islam moderat, Rahmatan Lil Alamin.